Analysis of Dynamic Characteristics of the Economic Systems in the Region of the CIS - Vladimir Aleksandrovich Plotnikov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Different regions of the world have a certain specificity of construction, operation and development of economic systems, which is determined by similar cultural, political, natural, historical, legal and other factors. Research interest is the identification of the specifics in the Subregion. Object of study authors are regional characteristics of the economies of the former Soviet Union, the Commonwealth of Independent States (CIS), which were formed largely under the influence of the same, common to them, the history of development of the single national economic complex of the Soviet Union. The subject of the study are the structural features of employment in the economies of the CIS countries and their impact on other characteristics of the economic systems of these countries. As the input data used for the analysis of long time series of macroeconomic indicators, available at the time of the survey, in 24 years: from 1990 to 2013. Investigated and compared, using the author’s methodology, the data on GDP, employment, investment and savings. On the basis of the selected dependencies, directly reflecting the performance of the national economy, the central place among which allocated the type of employment (flexible and rigid, the latter, in turn, classified into direct and inverse), explores trends in the economic development of the countries of the CIS region. As a result, proposed classification of these countries, based on comparative analysis of the characteristics of their economies. The classification is based on a number of interdependencies: type of employment and productivity; dynamics of GDP, investment and savings; the ratio of investment and savings. The results can be used in the development and implementation of public policy by governments in the CIS region.